Thamnīap samāchik Saphā Phūth̄æn Rātsad̨̄on : dairap l̄ưaktang m̄ưa wanthī 17 Phrưtsačhikāyon, Ph̨̄o. S̨̄o. 2539 (Fāi Phalit ʻĒkkasān Ratthasaphā, K̨̄ong Kānprachāsamphan, Samnakngān Lēkhāthikān Saphā Phūth̄æn Rātsad̨̄on, 1999)
Directory of the members of the House of Representatives, Thailand, elected on 17th November 1996.